One-Stage High-Density Focal Stereo-Array SEEG-Guided Radiofrequency Thermocoagulation for the Treatment of Pediatric Giant Hypothalamic Hamartomas - Wang, Min; Zhou, Yuanfeng; Zhang, Yi; Shi, Wei; Zhou, Shuizhen; Wang, Yi; Li, Hao; Zhao, Rui (Frontiers in Neurology, 2020)
Background: Giant hypothalamic hamartomas (HHs) are extremely rare lesions, for which the treatment is challenging. While minimally invasive treatments such as radiofrequency thermal coagulation and laser ablation have improved seizure outcomes, multiple operations are often required. This study investigated the value of one-stage stereo-array radiofrequency thermocoagulation based on stereotactic electroencephalography (SEEG) for pediatric giant HHs. Methods: We analyzed the clinical data of six patients with giant HHs (masses with a maximum diameter >30 mm) who underwent stereotactic electrode implantation between November 2017 and April 2019. After a multidisciplinary discussion, we designed a high-density focal stereo-array electrode implantation strategy. SEEG-guided bipolar coagulations were performed between two contiguous contacts of the same electrode, or between two adjacent contacts of different electrodes. Results: Among the six patients, three were male and three were female, with an average age of 5.08± 4.73 years (range, 1.4–12 years); the average follow-up duration was 20.17±5.49 months. One patient had previously undergone open surgery. Four patients had gelastic sezures, one had gelastic and tonic seizures, and one had gelastic and generalized tonic-clonic seizures. The number of implanted electrodes ranged from 3 to 7, with an average of 5.33. One patient had transient diabetes insipidus after the operation, and no child had fever or new hormone metabolisms disorder after surgery. Four patients had Engel I classification outcomes (free from disabling seizures), and two patients had Engel Ⅱ classification outcomes. Conclusion: Although the exploration of epileptic activity and the extent of ablation are limited by the number of SEEG electrodes for the complete disconnection. One-stage high-density focal stereo-array SEEG-guided radiofrequency was safe and effective for treating pediatric giant HH patients. It can be an alternative method to treat giant HHs where LITT is unavailable.